The effect of oromotor therapy on the suction reflex in low birth weight infants and mother's self-efficacy - Yuni Karomah; Kurnia Wijayanti; Nopi Nur Khasanah (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Low birth weight (LBW) infants are at risk of impaired sucking reflexes due to the immaturity of the oromotor system, which can affect nutritional intake and increase morbidity. Maternal involvement in the care of LBW infants is strongly influenced by maternal self-efficacy. One intervention that can be applied is oromotor therapy using the Premature Infant Oral Motor Intervention (PIOMI) method. Purpose: To analyze the effect of oromotor therapy on the sucking reflex of LBW infants and maternal self-efficacy. Method: This study employed a quantitative pre-experimental design with a one-group pretest–posttest without control approach. The sample consisted of 17 mother–infant dyads of LBW infants treated in the NICU of Dr. Kariadi General Hospital, Semarang, selected using purposive sampling. The PIOMI intervention was administered for 7 days. Infant sucking reflex was measured using the Neonatal Oral-Motor Assessment Scale (NOMAS), while maternal self- efficacy was assessed using the Perceived Maternal Parenting Self-Efficacy (PMP-SE) questionnaire. Data were analyzed using the Wilcoxon test. Results: The results demonstrated a significant improvement in infant sucking reflex and maternal self-efficacy after the PIOMI intervention, with statistically significant differences (p < 0.05). Conclusion: PIOMI oromotor therapy is effective in improving the oromotor function of LBW infants and enhancing maternal confidence in infant care.